Aspectos morfologicos y biologia de Davara caricae Dyar (Lepidoptera; Phycitidae) - Monteagudo Toranzo, S.=700 1 Carracedo Gonzalez, C.; Mirabal Rodriguez, R.; Ruiz Machado, M.
(En, Es)
ilus., 7 ref.
Keywords: INSECTA; LEPIDOPTERA; ANATOMIA ANIMAL; ZOOLOGIA; CUBA; DAVARA CARICAE